2018
DOI: 10.1186/s12966-018-0738-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal concern about child’s weight and related behaviours and maternal weight-related parenting practices: a cross-sectional study

Abstract: BackgroundParents influence their children’s weight-related behaviours through their parenting practices, which are often a focal point of obesity prevention interventions. This study examined associations of maternal concern about their child’s weight, dietary intake, physical activity, and media use with maternal food, physical activity, and media parenting practices.MethodsMothers (n = 310) reported their level of concern regarding their child’s weight and related behaviours and their weight-related parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 34 publications
3
47
2
1
Order By: Relevance
“…Parents awareness regarding their child's overweight risk would have ideally resulted in preventive actions to reduce this risk, such as offering healthier foods to their child. However, studies have shown that greater concern about child's overweight risk was associated with unfavorable parental strategies [31,32] or with a lack of action to prevent weight gain in their children [33]. Developing practical healthy tools for parents might be useful to improve their child's diet in relation to such concerns.…”
Section: Parental Concerns-overweightmentioning
confidence: 99%
“…Parents awareness regarding their child's overweight risk would have ideally resulted in preventive actions to reduce this risk, such as offering healthier foods to their child. However, studies have shown that greater concern about child's overweight risk was associated with unfavorable parental strategies [31,32] or with a lack of action to prevent weight gain in their children [33]. Developing practical healthy tools for parents might be useful to improve their child's diet in relation to such concerns.…”
Section: Parental Concerns-overweightmentioning
confidence: 99%
“…These results are of interest as previous research suggests that parental weight status is a predictor of the use of coercive FPPs [54]. Parents who struggle with their own eating and weight are more likely to use coercive FPPs with their children [69,96,97] and adolescents [85]. However, the results in the current review, that there appears to be no difference between parental weight and use of coercive FPPs, suggests otherwise.…”
Section: Discussionmentioning
confidence: 47%
“…Children's average anthropometric measurements at birth and those now were (respectively; at birth and now) body weight: 3148.0±647. 7 In the study; mothers' mealtime behaviors were presented in Table 1 according to children's characteristics. The first three behaviors with the highest scores in mother mealtime behaviors were daily fruit and vegetable availability, positive persuasion and snack-limits.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 The relevant literature reported that as feeding practices, mothers mostly try to control children's body weight by restricting food intake or forcing them to eat less or by increasing or decreasing children's direct food intake. 2,[4][5][6][7][8][9] The previous studies especially stated that these practices of mothers are associated with children's weight, restricting behaviors may result in overweightness but repressive practices of mothers may result in low weight in children. 2,[4][5][6]9,16,28 In the current study; mothers were found to have used restrictive and repressive behaviors and practices mostly, to have limited children's eating, drinking and snack amounts, to have increased daily fruit and vegetable consumption and to have used positive persuasion in order to encourage children to eat.…”
Section: Discussionmentioning
confidence: 99%